Marie Duval : maverick Victorian cartoonist - Grennan, Simon (Interventions: Rethinking the Nineteenth Century Ser., 2020)
Marie Duval: maverick Victorian cartoonist offers the first critical appraisal of the work of Marie Duval 1847-1890), one of the most unusual, pioneering and visionary cartoonists of the later nineteenth century, focusing on new types of cultural work by women and establishing Duval as a unique but exemplary figure in a transformational period of the nineteenth century.